2022
DOI: 10.1038/s41467-022-28062-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the COPD alveolar niche using single-cell RNA sequencing

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of death worldwide, however our understanding of cell specific mechanisms underlying COPD pathobiology remains incomplete. Here, we analyze single-cell RNA sequencing profiles of explanted lung tissue from subjects with advanced COPD or control lungs, and we validate findings using single-cell RNA sequencing of lungs from mice exposed to 10 months of cigarette smoke, RNA sequencing of isolated human alveolar epithelial cells, functional in vitro m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
102
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 82 publications
13
102
0
Order By: Relevance
“…Quantitative analysis of the cell numbers for each of 25 clusters in age-matched groups revealed IPF-associated changes in ageing human lungs in both cohorts (Figure 1 E). This reflects differences in location of tissue samples collected for scRNAseq analysis (Table 1) and matches reported in non-age matching studies contribution of different cell types to the total human lung cell population and alterations in IPF lung (20, 21, 24-26, 33, 34) Supplementary Table 2). Our data also uncovered changes in proportions of ageing human lung BEC and LEC populations between cohorts and conditions (Figure 1 E, Supplementary Table 3).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Quantitative analysis of the cell numbers for each of 25 clusters in age-matched groups revealed IPF-associated changes in ageing human lungs in both cohorts (Figure 1 E). This reflects differences in location of tissue samples collected for scRNAseq analysis (Table 1) and matches reported in non-age matching studies contribution of different cell types to the total human lung cell population and alterations in IPF lung (20, 21, 24-26, 33, 34) Supplementary Table 2). Our data also uncovered changes in proportions of ageing human lung BEC and LEC populations between cohorts and conditions (Figure 1 E, Supplementary Table 3).…”
Section: Resultssupporting
confidence: 66%
“…When applied to 12 ageing human lung BEC subpopulations, the dot plot expression analysis of markers of lung EC sub-types proposed in other transcriptional studies in human and murine tissues (35)(36)(37)(38)(39)(40) identified few distinct matches (Supplementary Figure 7). Further exploration of identities of 12 sub-populations by using these markers alongside those proposed for specific EC sub-clusters in HLCA and IPF cell atlas studies (20,21,(23)(24)(25), when coupled with module scoring (Figure 2 F) and cell cycle (Supplementary Figure 8) analyses, confirmed these matches, whilst 4 sub-clusters remained unannotated (Figure 2 F; Supplementary Figure 7). Altogether, these findings (Figure 2; Supplementary Figure 7) suggest that our study de-convoluted ageing human lung BEC population, providing advanced resolution of its heterogeneity at a transcriptional level, increasing the number of EC sub-clusters (20,21) and revealing previously underappreciated extend of diversity of ageing blood endothelium in human lung.…”
Section: Integrated Single-cell Rna Sequencing Analysis Reveals Heter...mentioning
confidence: 73%
See 2 more Smart Citations
“…Here we describe a computational package in R called Connectome which facilitates each of these tasks . Connectome has been used to explore native signaling in human lung 9 and to identify aberrant signaling in pulmonary arterial hypertension (PAH) 10 , chronic obstructive pulmonary disease (COPD) 11 , and COVID-19 12 .…”
Section: Introductionmentioning
confidence: 99%